2018
DOI: 10.1101/358291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of checkpoint kinase signalling and tumorigenesis by the NF-κB regulated gene, CLSPN

Abstract: Inhibition of the tumour promoting activities of NF-κB by cell signalling pathways has been proposed as a natural mechanism to limit the development of cancer. However, there has been a lack of evidence for these effects in vivo. Here we report that RelA T505A mice, where a CHK1 targeted Thr505 phosphosite is mutated to alanine, display earlier onset of MYC driven lymphoma than wild type littermates. We describe a positive feedback loop in which the NF-κB subunits RelA and c-Rel, in a manner dependent upon Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Therefore, the loss of CLSPN that is associated with SLF2 deficiency is in agreement with impaired CHK1 activation in SLF2 KO cells. Of note, a recent study provided genetic evidence that CLSPN‐deficient mice developed spontaneous B‐cell lymphomas (preprint: Hunter et al , 2018 ). Together, these findings indicate a mechanism by which CLSPN loss subsequent to SLF2 deficiency may explain the tumor suppressor function of SLF2, while SLF2 also acts as a regulator of several factors involved in cell cycle progression and DNA repair.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the loss of CLSPN that is associated with SLF2 deficiency is in agreement with impaired CHK1 activation in SLF2 KO cells. Of note, a recent study provided genetic evidence that CLSPN‐deficient mice developed spontaneous B‐cell lymphomas (preprint: Hunter et al , 2018 ). Together, these findings indicate a mechanism by which CLSPN loss subsequent to SLF2 deficiency may explain the tumor suppressor function of SLF2, while SLF2 also acts as a regulator of several factors involved in cell cycle progression and DNA repair.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas a subtle reduction of CHK1 activity is beneficial for the accumulation of tumor‐promoting mutations and drives tumorigenesis, full loss of CHK1 activity is toxic even for tumor cells due to the excessive and irrepressible level of DNA damage (Bric et al , 2009 ). This concept is empowered by a recent report revealing that deficiency for CLSPN, which act as fine‐tuner of CHK1 activity, resulted in spontaneous B‐cell lymphomagenesis (preprint: Hunter et al , 2018 ). Other than CHK1, the complete loss of the ATM/CHK2 axis is considered tumor‐promoting and the ATM locus is frequently affected by deletions of the long arm of chromosome 11 (Choi et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 16 BSAGs were found to be related with "DNA repair" and it was well known that de cits in DNA repair capacity might lead to genetic instability and carcinogenesis [49]. Recent study revealed that loss of a single allele of the CLSPN (claspin) gene in mice was su cient to drive earlier tumorigenesis [50]. And HELQ (Helicase, POLQ like) played a critical role for replication-coupled DNA repair, germ cell maintenance and tumor suppression in mammals [51].…”
Section: Molecular Evidence For the Peto's Paradox In Carnivores?mentioning
confidence: 99%